Concept of Offshore Financial Centers : In Search of an Operational Definition - Zorome, Ahmed (IMF Working Papers; Working Paper ;, 2007)
This paper proposes a new definition of Offshore Financial Centers (OFCs) and develops a statistical method to differentiate between OFCs and non-OFCs using data from the Coordinated Portfolio Investment Survey (CPIS), the International Investment Position (IIP), and the balance of payments. The suggested methodology identifies more than 80 percent of the OFCs in the study sample that also appear in the a priori list used by the IMF to conduct its OFC assessment program. The methodology distinguishes OFCs based strictly on their macroeconomic features and avoids subjective presumptions on their activities or regulatory frameworks. The study also identifies three new countries meeting OFC criteria.